GERAKAN “KACONG JHEBBING” PEMBURU AMAL JARIYAH UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN MENGHAFAL AL-QUR’AN DI DUSUN TAMBAK UKIR KECAMATAN TAMBAK UKIR - Hadi, Syamsul; Irfan, Agus; Fina, El; Ulfa, Maria; Ambarsari, Ida Fitriana (STKIP PGRI SITUBONDO, 2025)
This service aims to explore a Quranic tutoring program in Dusun Tambak Ukir, focusing on enhancing children's reading skills of the Quran, memorizing daily prayers, and fostering noble character. The initiative implements observations and surveys to gather comprehensive data. Results indicate that the tutoring significantly improves children's fluency in reading the Quran and aids them in memorizing important prayers. Additionally, the program plays a crucial role in character development, instilling values of kindness, respect, and responsibility within the community. By creating a supportive and engaging learning environment, this initiative not only promotes religious education but also strengthens social bonds among participants. The program emphasizes the importance of sustainability to ensure ongoing benefits and to encourage a culture of learning and moral development within the community.